SOCIAL WORK EDUCATORS’ PERCEPTIONS OF THE IMPORTANCE AND RELEVANCE OF ENVIRONMENTAL SOCIAL WORK - Arkert, Linda; Jacobs, Issie (Social Work, 2023)
It is well known that the effects of climate change and especially environmental inequality are amplified for people who live in poverty or who are marginalised. Social workers internationally and nationally are therefore becoming duty-bound to engage with the issue of environmental social work. This qualitative study used a descriptive design to explore and describe the perceptions of social work educators of the importance and relevance of environmental social work in South Africa. Purposive sampling was used to sample six social work educators from different universities. Semi-structured interviews were incorporated to obtain the data, which was thematically analysed. The results indicated that social work educators perceived ESW as important and relevant, and indicated that ways of integrating it into the social work curriculum should be explored further.